Efficacy of a "Rescue" Ciprofloxacin-Based Regimen for Eradication of Helicobacter pylori Infection after Treatment Failures. (14th May 2012) - Dore, Maria Pina; Tadeu, Vincenza; Are, Bianca; Mura, Ida; Fanciulli, Giuseppe; Massarelli, Giovannino; Piana, Andrea
Abstract : The aim of our study was to evaluate the efficacy and tolerability of a ciprofloxacin-based regimen for H. pylori eradication failures as an alternative to bismuth based quadruple therapy. Methods . Design: prospective single-center study. Patients in whom a first eradication trial with omeprazole/esomeprazole, clarithromycin plus amoxicillin or tinidazole/metronidazole had failed were included. H. pylori status: established by histology, rapide urease test and polymerase chain reaction. Intervention: esomeprazole 20 mg, ciprofloxacin 500 mg, and metronidazole 500 mg, administered together before breakfast and dinner for 10 days. Susceptibility testing was performed by the Epsilometer test. Ciprofloxacin resistance was defined as a MIC of ≥1 μ g/mL. Eradication was established by a negative 13C-UBT and 4–6 weeks post-therapy. Efficacy and side effects were determined. Results . 34 patients were enrolled, 32 completed the study. Compliance was excellent (100%). Side effects were mild. Ciprofloxacin-based therapy cured 65% (22/34) of patients by intention to treat and 69% (22/32) per protocol analysis. The prevalence of ciprofloxacin resistance was 8%. Conclusions . The effectiveness of ciprofloxacin-based therapy was greatly reduced despite the high prevalence of ciprofloxacin sensitive H. pylori strains. Bismuth based quadruple therapy still remain the best choice as a "rescue" regimen in our region.